Complete mitochondrial genome of the freshwater fish Onychostoma lepturum (Teleostei, Cyprinidae): genome characterization and phylogenetic analysis - Wang, I-Chen (Zookeys, 2020)
The cyprinid genus Onychostoma Günther, 1896 consists of 24 valid species distributed in Southeast Asia, including Taiwan, Hainan, mainland China and the Indochina region. In the present study, we determined the complete mitochondrial genome of O. lepturum, which is 16,598 bp in length, containing 13 protein-coding genes, two rRNA genes, 22 tRNA genes and a typical control region (D-loop). To verify the molecular phylogeny of the subfamily Acrossocheilinae, we provide new insights to better understand the taxonomic status of Acrossocheilus, Onychostoma and Folifer brevifilis. The phylogenetic trees presented three major clades based on the 13 protein-coding genes from 28 Acrossocheilinae species. Clades I and II represent the Onychostoma and Acrossocheilus groups, respectively. Species of Acrossocheilus, Onychostoma and F. brevifilis are included in Clade III, which is considered as an ancestral group. This work provides genomic variation information and improves our understanding of the Acrossocheilinae mitogenome, which will be most valuable in providing new insights for phylogenetic analysis and population genetics research.